2018
DOI: 10.1080/13803395.2018.1529229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neuropsychological performance in Mexico City youth using the Cambridge Neuropsychological Test Automated Battery (CANTAB)

Abstract: Background:The Cambridge Neuropsychological Test Automated Battery (CANTAB) is a computerized tool used to measure cognitive function in diverse populations, and is sensitive for assessing developmental changes in children. Although CANTAB has been used in several countries, its applicability in a Mexican child population is unknown. This study examined developmental trends on CANTAB in a large sample of urban Mexico City youth, and tested the hypothesis that their performance would be similar to a large Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…Boys responded faster without making more (or fewer) mistakes than girls. This is in line with others who did not find sex differences on the DMS accuracy (Green et al, 2019;Luciana & Nelson, 1998). Yet, we reported not only on accuracy but on response latency as well, which explains the differences in findings, i.e., an effect of sex on response latency.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Boys responded faster without making more (or fewer) mistakes than girls. This is in line with others who did not find sex differences on the DMS accuracy (Green et al, 2019;Luciana & Nelson, 1998). Yet, we reported not only on accuracy but on response latency as well, which explains the differences in findings, i.e., an effect of sex on response latency.…”
Section: Discussionsupporting
confidence: 93%
“…Further support for content validity (i.e., the test measures what is said to be measured) is found in, for instance, Green and colleagues (2019) who administered the DMS in a group of 5-15 years old children from Mexico City. Green et al (2019) found in line with the above researchers that DMS scores continue to improve (linearly) into adolescence, i.e., up until age 15 years old. They found for instance, that children aged 5 produced on average approximately 60% correct solutions on the DMS test, whereas children, e.g., aged 7 scored approximately 74% correct solutions.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…We also developed, and added to the data set, variables representing two of Caspi et al’s [ 5 ] measures of executive functioning, the Trail Making Test-B (TMT-B) and the Cambridge Neuropsychological Test Automated Battery—Rapid Visual Information Processing task (CANTAB: RVIP). We developed these data based on the correlations between the two executive functioning measures and externalising, internalising and the p -factor from Caspi et al’s [ 5 ] revised bifactor model, as well as correlations found within the literature between the two executive functioning variables, and adult measures of IQ [ 36 , 37 , 38 ]. To illustrate how S-1 bifactor models can facilitate the interpretation of novel findings, we also developed a second set of data for the TMT-B and the CANTAB: RIVP.…”
Section: Methods and Analysesmentioning
confidence: 99%